GENETIC PARAMETERS FOR GROWTH AND REPRODUCTIVE TRAITS OF BROWN SWISS CATTLE FROM MEXICO - Chin Colli, Ricardo Del Carmen; Estrada-León, Raciel; Magaña-Monforte, Juan; Segura-Correa, José Candelario; Núñez-Domínguez, Rafael (Ecosistemas y Recursos Agropecuarios, 2015)
The aim of this study was to estimate the components of (co)variance and genetic parameters for birth weight (BW, n = 16 806), weaning weight adjusted to 240 d of age (WW240, n = 9 011), yearling weight (YW, n = 6 516), age at first calving (AFC, n = 5 974) and calving interval (CI, n = 8 873) of Brown Swiss cattle from Mexico. Retrospective data from 1982 to 2010 were used from 86 ranches, spread across the country, which belonged to the Mexican Association of Registered Brown Swiss Cattle Breeders. Two trivariate analyzes were used considering BW- WW240-YW and YW-AFC-CI traits. The animal model included the contemporary group, direct additive, maternal additive, permanent environmental effects and the error term, plus age of cow at calving, parity and purebred degree as covariates. In general, direct heritabilities ranged from 0.03 to 0.35 and maternal heritabilities from 0.02 to 0.10. Correlations between direct and maternal additive genetic effects for BW, WW240 and YW ranged from -0.29 to -0.70. The direct genetic correlations for BW-WW240, BW-YW and WW240-YW were 0.51, 0.44 and 0.84, respectively, whereas for YW-AFC, YW-CI and AFC-CI they were -0.34, 0.14 and -0.26, respectively. In conclusion, selection for yearling weight could reduce the age at first calving without altering the calving interval.
Keywords: Brown Swiss; heritability; genetic correlation